If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying H + -1(-7) = 12 Multiply -1 * -7 H + 7 = 12 Reorder the terms: 7 + H = 12 Solving 7 + H = 12 Solving for variable 'H'. Move all terms containing H to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + H = 12 + -7 Combine like terms: 7 + -7 = 0 0 + H = 12 + -7 H = 12 + -7 Combine like terms: 12 + -7 = 5 H = 5 Simplifying H = 5
| 4x+2x=13.50 | | -6(a+8)+6(1-8)=-78 | | 7x-5=5x+8 | | -7x-4-4x=9x+4x | | (x^2+10+25)-5=25 | | 2[a-4]+15=13 | | 1x^2=0 | | 5x+2x-5=30 | | 10+3x-4=18 | | 4[2a+2]-17=15 | | .2(y+3)+3=.1(7y-4)-5 | | 6+6x=1+x | | 5x-9y-11x-y= | | 5[3x+12]=-15 | | -15=-20y | | 3[t-12]=27 | | -4x+3[2x-5]=31 | | 62=3(-6+6a)+4(a-2) | | h=-16t^2+31t+s | | 0=2y+8 | | 5[b+4]-6b=-24 | | 87=-3x+5 | | 3x*x+3x=7 | | -8x+7=7x+11 | | 18=-4a | | 10u-4u+9t-2t= | | -w+4[w+3]=-12 | | 60-2(2x-2)=4(x+2)+6x | | (x-1)(6x+2)=(2x+8)(3x-6) | | -(5x-5)-(6x-5)+9=-9(x-1)-(5x+8)+3 | | 2+4X=4-(x-3) | | 2[m+1]=16 |